Detection of helicobacter pylori in gastric biopsies with urease test and histopathologic assays - Murat B. ALKANAT; Osman ZEKİOĞLU and Ahmet AYDIN and Müge TUNÇYÜREK (Turkish Journal of Gastroenterology, 2020)
-